Cross‐species identification of a plasma microRNA signature for detection, therapeutic monitoring, and prognosis in osteosarcoma. (17th March 2015) - Allen‐Rhoades, Wendy; Kurenbekova, Lyazat; Satterfield, Laura; Parikh, Neha; Fuja, Daniel; Shuck, Ryan L.; Rainusso, Nino; Trucco, Matteo; Barkauskas, Donald A.; Jo, Eunji; Ahern, Charlotte; Hilsenbeck, Susan; et al.
<x xml:space="preserve">Abstract</x> We use a genetically engineered mouse model of osteosarcoma (OS) to perform cross‐species identification and validation of plasma microRNAs that can be utilized as novel biomarkers for detection and responsiveness to therapy. Our study is also the first to identify a plasma microRNA with prognostic significance in OS. Therefore, these studies have identified novel noninvasive biomarkers for OS that have the potential to impact the care and management of patients with this highly aggressive disease. <boxed-text content-type="graphic" id="cam4438-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>